The vertical distribution of methane (CH4), nutrients and chlorophyll a in Maxwell Bay (King George Island, WAP) during ECA60 expedition in December 2023 - Lina Aleke Holthusen; Hermann W Bange; Damian L Arévalo-Martínez; Thomas Henry Badewien; Juan Höfer; Carolin Regina Löscher; Camila Marin-Arias; Jens Meyerjürgens; Isabell Schlangen; Oliver Wurl (PANGAEA, 2025)
An oceanographic field campaign was conducted at the research station Base Julio Escudero on King George Island, Western Antarctica Peninsula, between December 2023 and January 2024 (Expedition ECA60). In order to investigate the distribution and sea-air fluxes of CH4, as well as the occurrence of glacial meltwater filaments and their influence on CH4 dynamics, the sampling location was chosen in Collins Bay, in close proximity to the sea terminus of Collins Glacier. Discrete water samples for methane (CH4), nutrients (NO3-, NO2- and PO4 3-), and chlorophyll a (chl a) were collected between 16 and 28 December 2023 at a time-series station at depths of 1, 5, 10, 25, 50 and 100 m. CTD casts were conducted concurrent with discrete sampling and the wind speed was recorded at a weather station on King George Island. The CH4 samples were obtained in triplicate, preserved with an aqueous solution of mercury chloride (HgCl2) and measured using gas chromatography with a flame ionization detector. Samples for nutrient analysis were filtered through 0.22 μm syringe filters (GPF), stored at -20 °C, and measured spectrophotometrically. All NO?? concentrations were below the detection limit of the instrument and thus excluded from the data set. Chl a samples were filtered through a GF/F filter, stored at -20 °C and analysed fluorometrically.